2018
DOI: 10.4103/sajc.sajc_257_17
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care and end-of-life measure outcomes: Experience of a tertiary care institute from South India

Abstract: Introduction:Desisting from disease directed treatment in the past weeks of life is a quality criterion in oncology service. Patients with advanced cancer have unrealistic expectations from chemotherapy and hold on to it as a great source of hope. Many oncologists continue futile and unnecessary treatments, instead of conveying to the patients the lack of benefit, resulting in delayed referral for palliative care (PC).Materials and Methods:This is a retrospective analysis of case records from June 2014 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Two Indian studies showed that 86% of children with cancer received chemotherapy during the last month of their life, and 78% was referred after cancer-directed therapy was completed, which hindered palliative care access [91,92]. These studies mirrored palliative care referral practices in the Indian adult cancer settings [93][94][95][96][97]. Non-referral and late referral to palliative care in paediatric oncology in Malaysia, Nigeria, and Morocco led to poorly controlled symptoms, caregiver distress, and most of the children dying within a few weeks of palliative care referral [35,[98][99][100].…”
Section: Palliative Care Referral Practices In Paediatric Oncologymentioning
confidence: 99%
“…Two Indian studies showed that 86% of children with cancer received chemotherapy during the last month of their life, and 78% was referred after cancer-directed therapy was completed, which hindered palliative care access [91,92]. These studies mirrored palliative care referral practices in the Indian adult cancer settings [93][94][95][96][97]. Non-referral and late referral to palliative care in paediatric oncology in Malaysia, Nigeria, and Morocco led to poorly controlled symptoms, caregiver distress, and most of the children dying within a few weeks of palliative care referral [35,[98][99][100].…”
Section: Palliative Care Referral Practices In Paediatric Oncologymentioning
confidence: 99%